5-Aminosalicylic Acid Released from Mesalazine Tablet-Comparison of Pharmacokinetic Parameters between Japanese Patients with Ulcerative Colitis and Healthy Adults - Mitsuyama, K.; Harada, K.; Yamasaki, H.; Kuwaki, K.; Masuda, J.; Tsuruta, O.; Sata, M. (Asian Journal of Chemistry, 2012)
A slow release formulation of mesalazine (5-aminosalicylic acid, 5-ASA) is commonly used for ulcerative colitis. We aimed to compare the pharmacokinetic profile of 5-ASA in Japanese patients with ulcerative colitis (UC patients) and healthy adults received 2 g single dose of mesalazine tablets. Main outcome measures were plasma and urinary concentrations of 5-ASA and its major metabolite N-acetyl-5-aminosalicylic acid (Ac-5-ASA) up to 12 h post-dose. 5-Aminosalicylic acid maximum plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC0-inf) in ulcerative colitis patients: 5197 ± 3345 ng/mL and 24333 ± 11542 ng h/mL, respectively; in healthy adults: 7190 ± 5093 ng/mL and 23890 ± 12684 ng h/mL, respectively. Total urinary excretion rate of 5-ASA and Ac-5-ASA: 25.2 ± 6.8 % in ulcerative colitis patients; 18.0 ± 9.9 % in healthy adults. The pharmacokinetic profile of 5-ASA was comparable between Japanese ulcerative colitis patients and healthy adults.